The active complex electrode (ACE1) electrical impedance tomography system & anatomically inspired modeling of electrode-skin contact impedance - Mellenthin, Michelle M., author; Mueller, Jennifer L., advisor; Lear, Kevin, committee member; Krapf, Diego, committee member; Pezeshki, Ali, committee member (Colorado State University. Libraries, 2016)
Electrical Impedance Tomography (EIT) is a technique used to image the varying electrical properties of biological tissues or tissue conductivity and permittivity. There are many clinical uses of EIT, but as a newer imaging modality, there is interest in improving hardware to acquire EIT data, creating models of the system and generating high quality images. The two main contributions of this work include: (1) EIT hardware advancements and (2) software modeling to simulate measured human subject data. Specifically, this dissertation includes the design and testing of Colorado State University's first EIT system, the pairwise current injection active complex electrode (ACE1) system for phasic voltage measurement. The ACE1 system was primarily designed for thoracic EIT applications, and its performance and limitations were tested through a variety of experiments. Additionally, the EIT forward problem was used to investigate electrode-skin contact impedance.
Keywords: EIT; impedance; tomography; electrical; contact; system